Post-concussion syndrome and concussion incidence improved in a pro rugby player following cervical spine rehab: case study and 6-year follow-up - Seth Strauss; Douglas F Lightstone; Curtis Fedorchuk; Robert Pomahac; Paul A Oakley; Deed E Harrison (Concussion)
Aim: To report improvements in post-concussion syndrome and concussion incidence following cervical spinal alignment correction. Case presentation: A 27-year-old professional rugby player with 20 d...